Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{3}{4}.26\frac{1}{5}-\frac{3}{4}.44\frac{1}{5}\)
\(=\frac{3}{4}.\left(26\frac{1}{5}-44\frac{1}{5}\right)\)
\(=\frac{3}{4}.\left(-18\right)\)\(=\frac{-27}{2}\)
\(\frac{3}{4}.26\frac{1}{5}-\frac{3}{4}.44\frac{1}{5}\)
= \(\frac{3}{4}.\left(26\frac{1}{5}-44\frac{1}{5}\right)\)
= \(\frac{3}{4}\) . (-18)
= \(\frac{-27}{2}\)
\(\frac{3}{4}.26\frac{1}{5}-\frac{3}{4}44\frac{1}{5}\)
= \(\frac{3}{4}\left(26\frac{1}{5}-44\frac{1}{5}\right)\)
= \(\frac{3}{4}\left(26+\frac{1}{5}-44-\frac{1}{5}\right)\)
=\(\frac{3}{4}.\left(-18\right)\)
=-13,5
e) \(\frac{1}{7}.\frac{-3}{8}+\frac{-13}{8}.\frac{1}{7}\)
\(=\frac{1}{7}.\left[\left(-\frac{3}{8}\right)+\left(-\frac{13}{8}\right)\right]\)
\(=\frac{1}{7}.\left(-2\right)\)
\(=-\frac{2}{7}.\)
Chúc bạn học tốt!
1.
a.
\(\frac{1}{3}+\left(\frac{1}{5}-\frac{1}{7}\right)\)
\(=\frac{1}{3}+\frac{1}{5}-\frac{1}{7}\)
\(=\frac{35-21-15}{105}\)
\(=-\frac{1}{105}\)
b.
\(\frac{3}{5}-\left(\frac{3}{4}-\frac{1}{2}\right)\)
\(=\frac{3}{5}-\frac{3}{4}+\frac{1}{2}\)
\(=\frac{12-15+10}{20}\)
\(=\frac{7}{20}\)
c.
\(\frac{4}{7}-\left(\frac{2}{5}+\frac{1}{3}\right)\)
\(=\frac{4}{7}-\frac{2}{5}-\frac{1}{3}\)
\(=\frac{60-42-35}{105}\)
\(=-\frac{17}{105}\)
2.
a.
\(S=-\frac{1}{1\times2}-\frac{1}{2\times3}-\frac{1}{3\times4}-...-\frac{1}{\left(n-1\right)\times n}\)
\(S=-\left(\frac{1}{1\times2}+\frac{1}{2\times3}+\frac{1}{3\times4}+...+\frac{1}{\left(n-1\right)\times n}\right)\)
\(S=-\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{n-1}-\frac{1}{n}\right)\)
\(S=-\left(1-\frac{1}{n}\right)\)
\(S=-1+\frac{1}{n}\)
b.
\(S=-\frac{4}{1\times5}-\frac{4}{5\times9}-\frac{4}{9\times13}-...-\frac{4}{\left(n-4\right)\times n}\)
\(S=-\left(\frac{4}{1\times5}+\frac{4}{5\times9}+\frac{4}{9\times13}+...+\frac{4}{\left(n-4\right)\times n}\right)\)
\(S=-\left(1-\frac{1}{5}+\frac{1}{5}-\frac{1}{9}+\frac{1}{9}-\frac{1}{13}+...+\frac{1}{n-4}-\frac{1}{n}\right)\)
\(S=-\left(1-\frac{1}{n}\right)\)
\(S=-1+\frac{1}{n}\)
Chúc bạn học tốt
\(\frac{1}{2}+\frac{2}{3}-\frac{3}{4}+\frac{4}{5}-\frac{5}{6}+\frac{6}{7}+\frac{5}{6}-\frac{4}{5}+\frac{3}{4}-\frac{2}{3}+\frac{1}{2}\)
\(=\left(\frac{1}{2}+\frac{1}{2}+\frac{6}{7}\right)+\left(\frac{2}{3}-\frac{2}{3}\right)+\left(\frac{-3}{4}+\frac{3}{4}\right)+\left(\frac{4}{5}-\frac{4}{5}\right)+\left(\frac{-5}{6}+\frac{5}{6}\right)\)
\(=\frac{13}{7}+0+0+0+0\)
\(=\frac{13}{7}\)
\(\frac{1}{2}+\frac{2}{3}-\frac{3}{4}+\frac{4}{5}-\frac{5}{6}+\frac{6}{7}+\frac{5}{6}-\frac{4}{5}+\frac{3}{4}-\frac{2}{3}+\frac{1}{2}.\)
\(=\left(\frac{1}{2}+\frac{1}{2}\right)+\left(\frac{2}{3}-\frac{2}{3}\right)-\left(\frac{3}{4}-\frac{3}{4}\right)+\left(\frac{4}{5}-\frac{4}{5}\right)-\left(\frac{5}{6}-\frac{5}{6}\right)+\frac{6}{7}\)
\(=1+0-0+0+\frac{6}{7}\)
\(=1+\frac{6}{7}=1\frac{6}{7}\)
2: =>2x-1/4=5/6-1/2x
=>5/2x=5/6+1/4=13/12
=>x=13/30
3: =>3x-5/6=2/3-1/2x
=>3,5x=2/3+5/6=4/6+5/6=9/6=3,2
hay x=32/35
a) \(\frac{21}{47}+\frac{9}{45}+\frac{26}{47}+\frac{4}{5}\)
\(=\left(\frac{21}{47}+\frac{26}{47}\right)+\left(\frac{9}{45}+\frac{4}{5}\right)\)
\(=\frac{47}{47}+\left(\frac{1}{5}+\frac{4}{5}\right)\)
\(=1+1=2\)
b) \(12.\left(-\frac{2}{3}\right)^2+\frac{4}{3}\)
\(=12.\frac{4}{9}+\frac{4}{3}\)
\(=\frac{16}{3}+\frac{4}{3}\)
\(=\frac{20}{3}\)
c) \(12,5.\left(-\frac{5}{7}\right)+15.\left(-\frac{5}{7}\right)\)
\(=\left(-\frac{5}{7}\right).\left(12,5+15\right)\)
\(=\left(-\frac{5}{7}\right).27,5\)
\(=\left(-\frac{5}{7}\right).\frac{55}{2}\)
\(=-\frac{275}{14}\)
d) \(\frac{4}{5}.\left(\frac{7}{2}+\frac{1}{4}\right)^2\)
\(=\frac{4}{5}.\left(\frac{14}{4}+\frac{1}{4}\right)^2\)
\(=\frac{4}{5}.\left(\frac{15}{4}\right)^2\)
\(=\frac{4}{5}.\frac{225}{16}\)
\(=\frac{45}{4}\)
a)\(\frac{21}{47}+\frac{9}{45}+\frac{26}{47}+\frac{4}{5}\)
=\(\frac{21}{47}+\frac{1}{5}+\frac{26}{47}+\frac{4}{5}\)
=\(\left(\frac{21}{47}+\frac{26}{47}\right)+\left(\frac{1}{5}+\frac{4}{5}\right)\)
=\(\frac{47}{47}+\frac{5}{5}=1+1=2\)
b)\(12.\left(-\frac{2}{3}\right)^2+\frac{4}{3}\)
=\(12.\frac{4}{9}+\frac{4}{3}\)
=\(\frac{12}{1}.\frac{4}{9}+\frac{4}{3}=\frac{48}{9}+\frac{4}{3}\)
=\(\frac{16}{3}+\frac{4}{3}=\frac{20}{3}\)
c)\(12,5.\left(-\frac{5}{7}\right)+1,5.\left(-\frac{5}{7}\right)\)
=\(\left(-\frac{5}{7}\right).\left(12,5+1,5\right)\)
=\(\left(-\frac{5}{7}\right).14=\left(-\frac{5}{7}\right).\frac{14}{1}=-10\)
d)\(\frac{4}{5}.\left(\frac{7}{2}+\frac{1}{4}\right)^2\)
=\(\frac{4}{5}.\left(\frac{14}{4}+\frac{1}{4}\right)^2\)
=\(\frac{4}{5}.\left(\frac{15}{4}\right)^2\)
=\(\frac{4}{5}.\frac{225}{16}\)
=\(\frac{900}{80}=\frac{45}{4}\)
Nhớ tick cho mình nha!
Ta có: 3/4. 26/1/5 - 3/4.44/1/5
= 3/4.(26/1/5-44/1/5)
= 3/4.(26-44)
= 3/4. (-18)
= -27/2